Web marketing for the music business - Hutchison, Thomas W. (Focal Press, 2013)
Interested in promoting, selling, and distributing music online? Have the website but not sure what to do next? Web Marketing for the Music Business is designed to help develop the essential Internet presence needed for effective promotion, sales, and distribution. Author Tom Hutchison provides instructions on how to set up a website, as well as how to use the Internet to promote you or your client, and the website. Includes information on maximizing your site to increase traffic, online grassroots marketing tactics that will advance your career and how to best utilize social networking sites such as Facebook and Twitter. The accompanying website will keep you up-to-date, with online resources for web support. The author's blog is continuously updated to include the latest breaking techniques for promotion.